The allelopathic effect of Potentilla acaulis on the changes of plant community in grassland, northern China. Issue 1 (4th October 2014) - Zhang, Yujuan; Tang, Shiming; Liu, Kesi; Li, Xuefeng; Huang, Ding; Wang, Kun
Abstract: Changes in plant community composition may be driven partly by the traits of dominant species during succession. In degraded northern China grasslands, plant community composition has changed remarkably and previous studies have mostly focused on the effects of anthropogenic activities, ignoring the role of interspecific interactions. We hypothesized that Potentilla acaulis, a dominant plant in heavily degraded steppe landscapes, inhibits co‐occurring plant species by exuding allelopathic exudates that are inhibitory to establishing seedlings. Field vegetation surveys showed that mean heights and importance values of Stipa krylovii and Leymus chinensis were significantly lower in patches dominated by P. acaulis compared with patches dominated by S . krylovii . In germination experiments, P. acaulis extracts had significant allelopathic effects on three grass species ( S. krylovii, Artemisia frigida, and L. chinensis ) common in northern China grasslands. Allelopathic effects were a factor of exudate source, exudate concentration, and target species. Shoot growth of L. chinensis and A. frigida, extracts showed a "low‐promotion and high‐inhibition" effect, wherein low levels of exudate had a growth‐promoting effect, but higher concentrations had an increasingly inhibitory effect. S. krylovii was the most sensitive target species, and both its shoot and radicle growth were significantly reduced in the presence of P. acaulis. As with the other two targets, the magnitude of inhibition increased with increasing exudate concentration. Ecologically, this study suggests that allelopathy may contribute to the dominance of P. acaulis in degraded grasslands, which has important implications for recovery of other native plants in these degraded grasslands. The specific mechanism demands further investigation.